Student Satisfaction with Online Learning: A Study Among Medical Students at a Medical School in Northern Morocco During the COVID‑19 Pandemic - Bousgheiri, Fadila; Belafki, Hassana; Oulmaati, Abdallah; Elbouri, Hicham; Najdi, Adil (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2023)
Introduction: The COVID-19 pandemic has forced the use of e-learning. The aim of this study was to assess medical students’ experience with e-learning methods. Methods: We conducted a cross-sectional study, using a Google Forms questionnaire. Results: From a total of 303 participants, 75% of them rated the e-learning experience as good to excellent, and more than 46% considered that distance learning can be equivalent to face-to-face learning. Conclusion: The experience of e-learning should motivate and challenge us to improve our technological skills in order to adopt a modern and practical pedagogy.